(untitled) (LACCEI, 2024)
The methodology used in Industrial Chemistry subject of the 4th year Industrial Engineering based on active teaching methods, personalized follow-up, own elaboration of cases linked to the surrounding reality, use of resources and varied activities to cover different doors of knowledge and application metacognition thought routines, allowed to achieve highly satisfactory results for both teachers and students. The authentic evaluation strategies are oriented to reinforce the understanding of the current challenges of Engineering, trying to awaken a personal intrinsic motivation as a source of satisfaction of the achievements and real usefulness of learning for professional practice, all these distinctive notes of deep learning.